First detection of Echinococcus multilocularis in dogs in a highly endemic area of Poland - Karamon, Jacek; Samorek-Pierog, Malgorzata; Kochanowski, Maciej; Dabrowska, Joanna; Sroka, Jacek; Golab, Elzbieta; Umhang, Gérald; Cencek, Tomasz (Folia Parasitologica, 2016)
International audience The aim of the investigation was to estimate the epizootic situation concerning infection by the cestode Echinococcus multilocularis Leuckart, 1863 in dogs (Canis lupus familiaris Linnaeus) from a Polish region where this parasite is highly prevalent in red foxes. Faecal samples (n = 148) were collected from rural dogs in Podkarpackie Province. Samples were examined through nested PCR (for E. multilocularis), multiplex PCR (E. multilocularis, species of Taenia Linnaeus, 1758) and PCR [E. granulosus (Batsch, 1786)]. Specific products were sequenced. Faeces were also examined coproscopically. In samples from two dogs (1.4%), there were positive PCR results for E. multilocularis. Taenia-specific PCR products were found in nine dogs (6.1%). Sequencing identified Taenia serialis (Gervais, 1847), T. hydatigena Pallas, 1766, T. pisiformis (Bloch, 1780) and Hydatigera taeniaeformis (Batsch, 1786). One sample (0.7%) was identified as Mesocestoides litteratus (Batsch, 1786). All samples were negative for E. granulosus with PCR. Taking into account coproscopic and PCR results, 28% of dogs were infected with helminths (8% with tapeworms). It should be stressed that one of the infected with E. multilocularis dogs shed eggs of the Taenia type and had a habit of preying on rodents. This investigation revealed the presence of E. multilocularis in dogs for the first time in Poland.